Handbook of seafood quality, safety and health applications - Borges, Bruno Augusto Amato (Delve Publishing, 2017)
Seafood is any form of sea life regarded as food by humans. Seafood prominently includes fish and shellfish. Shellfish include various species of molluscs, crustaceans, and echinoderms. This book p resents latest advances in the science and technology of seafood quality and safety as well as new developments in the nutritional effects and applications of marine foods.--Provided by publisher.